Mitochondrial Population in Mouse Eosinophils: Ultrastructural Dynamics in Cell Differentiation and Inflammatory Diseases - Bonjour, Kennedy; Palazzi, Cinthia; Silva, Thiago P.; Malta, Kássia K.; Neves, Vitor H.; Oliveira-Barros, Eliane G.; Neves, Igor; Kersten, Victor A.; Fortuna, Bruno T.; Samarasinghe, Amali E.; Weller, Peter F.; Bandeira-Melo, Christianne; et al. (Frontiers in Cell and Developmental Biology, 2022)
Mitochondria are multifunctional organelles of which ultrastructure is tightly linked to cell physiology. Accumulating evidence shows that mitochondrial remodeling has an impact on immune responses, but our current understanding of the mitochondrial architecture, interactions, and morphological changes in immune cells, mainly in eosinophils, is still poorly known. Here, we applied transmission electron microscopy (TEM), single-cell imaging analysis, and electron tomography, a technique that provides three-dimensional (3D) views at high resolution, to investigate mitochondrial dynamics in mouse eosinophils developing in cultures as well as in the context of inflammatory diseases characterized by recruitment and activation of these cells (mouse models of asthma, H1N1 influenza A virus (IAV) infection, and schistosomiasis mansoni). First, quantitative analyses showed that the mitochondrial area decrease 70% during eosinophil development (from undifferentiated precursor cells to mature eosinophils). Mitophagy, a consistent process revealed by TEM in immature but not in mature eosinophils, is likely operating in mitochondrial clearance during eosinophilopoiesis. Events of mitochondria interaction (inter-organelle membrane contacts) were also detected and quantitated within developing eosinophils and included mitochondria-endoplasmic reticulum, mitochondria-mitochondria, and mitochondria-secretory granules, all of them significantly higher in numbers in immature compared to mature cells. Moreover, single-mitochondrion analyses revealed that as the eosinophil matures, mitochondria cristae significantly increase in number and reshape to lamellar morphology. Eosinophils did not change (asthma) or reduced (IAV and Schistosoma infections) their mitochondrial mass in response to inflammatory diseases. However, asthma and schistosomiasis, but not IAV infection, induced amplification of both cristae numbers and volume in individual mitochondria. Mitochondrial cristae remodeling occurred in all inflammatory conditions with the proportions of mitochondria containing only lamellar or tubular, or mixed cristae (an ultrastructural aspect seen just in tissue eosinophils) depending on the tissue/disease microenvironment. The ability of mitochondria to interact with granules, mainly mobilized ones, was remarkably captured by TEM in eosinophils participating in all inflammatory diseases. Altogether, we demonstrate that the processes of eosinophilopoiesis and inflammation-induced activation interfere with the mitochondrial dynamics within mouse eosinophils leading to cristae remodeling and inter-organelle contacts. The understanding of how mitochondrial dynamics contribute to eosinophil immune functions is an open interesting field to be explored.